ASSESSMENT OF THE CURRENT STATE OF INFORMATICS AND PROGRAMMING TEACHING FROM THE STUDENTS` POINT OF VIEW - ZAHOREC, Jan; HASKOVA, Alena (Journal of Technology and Information Education, 2009)
In their paper the authors present a part of their research results, they obtained within a broader research focused on possibilities to influence students' attitudes and approaches to particular subjects, mainly the less favourite ones. On the background of the obtained results they discuss here students' interest in study informatics and programming and try to identify the reasons of students' interest or disinterest in these subjects. They try to answer the question what are currently the most powerful motivation factors for students to acquire new knowledge from these areas.
Keywords: teaching subjects; students` attitude towards partial subjects; favourite subjects; natural science subjects; physics; informatics; programming; interest in study informatics and programming; motivation factors